2010
DOI: 10.1002/cphc.201000157
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Tunable Micron‐Bubbles Based on Fluorous–Fluorous Interactions of Perfluorinated Dendritic Polyglycerols

Abstract: This paper describes the behavior of various generations of polyglycerol dendrimers that contain a perfluorinated shell. The aggregation in organic solvents is based on supramolecular fluorous-fluorous interactions, which can be described by means of (19)F NMR spectroscopy. In order to study the interaction and aggregation phenomena of dendrimers with perfluorinated shell and perfluoro-tagged guest molecules we investigated [G3.5]-dendrimer with a perfluorinated shell in the presence of perfluoro-tagged disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Hyperbranched polyglycerol 4f that contains a perfluorinated core, however, was able to enhance the solubility of a perfluoro tagged diazo dye in water, based on supramolecular fluorous–fluorous interactions as observed by UV‐vis measurement (see Supporting Information Figure S1) 24, 25…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperbranched polyglycerol 4f that contains a perfluorinated core, however, was able to enhance the solubility of a perfluoro tagged diazo dye in water, based on supramolecular fluorous–fluorous interactions as observed by UV‐vis measurement (see Supporting Information Figure S1) 24, 25…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work on dendritic architectures for the solubilization of hydrophobic drugs, we studied hyperbranched polymer‐based core–shell architectures possessing linear and branched outer shells 19–23. Perfluoroalkyl shell architectures have also been reported 24, 25. Furthermore, we have demonstrated that hyperbranched polyglycerols modified with different functionalized aromatic cores can encapsulate the hydrophobic guests by specific interaction such as π–π interactions 26.…”
Section: Introductionmentioning
confidence: 97%
“…To generate the perfectly branched generation 4 ([G4]) dendrimer, we applied a reaction sequence similar to the one previously reported. [43] The synthesis is based on an iterative two-step protocol which includes allylation of an alcohol and subsequent catalytic dihydroxylation of the allylic double bond. In contrast to the procedure published earlier, we modified the synthesis in the catalytic dihydroxylation step.…”
Section: Polyglycerol Dendrimer Generation 4 (Dpg 100 )mentioning
confidence: 99%
“…Polyglycerol dendrimers that contain a perfluorinated shell have previously been synthesized 13 and analyzed with respect to their aggregation behavior. 14 These dendritic polymers have been employed as a supramolecular, homogeneous support for a perfluoro-tagged Pd catalyst in Suzuki coupling. 13 Also the influence of perfluoroalkyl tails in the self-assembly of classical surfactants is well documented in the literature.…”
Section: Introductionmentioning
confidence: 99%